Learning, inflation expectations and optimal monetary policy - Eric Schaling (Bank of Finland, 2003)
In this paper we analyse disinflation policy in two environments. In the first, the central bank has perfect knowledge, in the sense that it understands and observes the process by which private sector inflation expectations are generated; in the second, the central bank has to learn the private sector inflation forecasting rule.With imperfect knowledge, results depend on the learning scheme that is employed.Here, the learning scheme we investigate is that of least-squares learning (recursive OLS) using the Kalman filter.A novel feature of a learning-based policy as against the central bank's disinflation policy under perfect knowledge is that the degree of monetary accommodation (the extent to which the central bank accommodates private sector inflation expectations) is no longer constant across the disinflation, but becomes state-dependent.This means that the central bank's behaviour changes during the disinflation as it collects more information.
URN:NBN:fi:bof-20140807421
Keywords: C53; E43; E52; F33; 330; learning; rational expectations; separation principle; Kalman filter; time-varying parameters; optimal control